POLISHING TECHNOLOGICAL PARAMETERS INFLUENCE LAW STUDY ON TC4 MATERIAL CUTTING DEPTH FOR ABRASIVE CLOTH WHEEL - HUAI WenBo; WANG XuHui; NIU QinHua; LIN XiaoJun (Jixie qiangdu)
The blade surface of milling-formed aero-engine blisk is a free-form surface with large curvature variation,which seriously restricts the uniformity of polished surface. In order to master the influence rule of the flexible polishing technological parameters for abrasive cloth wheel on materials cutting depth,the single factor polishing experiment of TC4 specimen was carried out based on the polishing technological equipment of “NC machine + flexible grinding head + elastic grinding tool（ abrasive cloth wheel） ”,the process parameters influence on materials cutting depth was analyzed,and the materials cutting depth prediction model was established by orthogonal test,the results show that the cutting depth is the most sensitive to the amount of compression,the more sensitive to the rotational speed,the less sensitive to the feed speed and the less sensitive to abrasive size. Finally,the polishing experiment was carried out,it’s results show that the measured contour is consistent with the predicted contour,and the prediction model is reliable and can be used to predict the materials cutting depth.